Supportif Edukatif Berbasis Keluarga Berhubungan dengan Penurunan Fungsi Kognitif pada Lansia - Faizatus Shafiyah; Cory Nelia Damayanti; Syaifurrahman Hidayat; Yulia Wardita (Fakultas Ilmu Kesehatan, 2022)
This study aims to determine the relationship between family-based educational support and cognitive decline in the elderly in the coastal village of Sumenep Regency, Batangbatang, East Legung. This research was conducted for three months, from May to July 2021. The subjects of this study were 60-70 years old who lived with their families. The research method is a cross-sectional study. This study uses a sampling technique based on distrust through purposeful sampling. Data was collected using a questionnaire and a mini-test from the Mental State Survey using the Spearman's Rank Statistical Test. As a result, of the 40 respondents, an average of 30 (75.0%) of the total respondents were elderly who received adequate family education support, and it was found that the majority of the elderly experienced moderate cognitive decline, namely 28 (70.0%) with a ranking test. Spearman's results with a value of 0.001. In conclusion, there is a relationship between family education support and cognitive decline in the coastal elderly in the villages of Sumenep, Batangbatang, and Legung Timur districts